2023
DOI: 10.1037/tra0001332
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among university employees during the COVID-19 pandemic: The role of previous life trauma and current posttraumatic stress symptoms.

Abstract: Objective: Previous studies indicated that the coronavirus disease 2019 (COVID-19) pandemic has harmed the mental health of diverse samples. Adopting a trauma lens with a sample of university faculty and staff, this study examined risk conferred by previous exposure to traumatic life events (TLE) on pandemic-related mental health harm (MHH) and stress and the mediating influence of posttraumatic stress disorder (PTSD) symptoms. Method: In Spring 2021, employees (N = 641) of a public university in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
2
3
0
1
Order By: Relevance
“…That is, we did not find evidence for a stronger longitudinal association between COVID-19 stress and mental health symptoms in women than men. These results are consistent with results of previous studies that also failed to find a moderating effect of gender in the relation of COVID-19 stress and mental health (e.g., Goldstein et al, 2023) or in the relation of general types of stress and mental health (e.g., Kendler et al, 2003;van Loo et al, 2018). Similarly, in their multivariate model of university instructors' well-being during COVID-19, Jelińska and Paradowski (2021) failed to find a significant gender effect once other mental health and COVID-19 impacts were included.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…That is, we did not find evidence for a stronger longitudinal association between COVID-19 stress and mental health symptoms in women than men. These results are consistent with results of previous studies that also failed to find a moderating effect of gender in the relation of COVID-19 stress and mental health (e.g., Goldstein et al, 2023) or in the relation of general types of stress and mental health (e.g., Kendler et al, 2003;van Loo et al, 2018). Similarly, in their multivariate model of university instructors' well-being during COVID-19, Jelińska and Paradowski (2021) failed to find a significant gender effect once other mental health and COVID-19 impacts were included.…”
Section: Discussionsupporting
confidence: 93%
“…In a survey of over 1,700 faculty, staff, and students at the University of Massachusetts at Amherst, 51% of staff and 45% of faculty reported high levels of “stress,” loneliness, and physical health problems in the months following the onset of the pandemic (Deznabi et al, 2020). Similar reports of “stress” (42.3%) were found in a survey of 641 faculty and staff at the University of Chicago (Goldstein et al, 2023). In this latter study, 36% of employees screened positive for posttraumatic stress disorder.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Faculty, staff, and students had to quickly adjust to new circumstances, including how individuals teach and learn, how they collaborate with others, and how they juggle their personal and professional lives [ 125 , 126 ]. This along with the turbulence and uncertainty due to the pandemic did have its toll on the well-being of faculty, with reports of worrying symptoms of anxiety, depression, and stress [ 127 , 128 , 129 , 130 ], sometimes with younger individuals, the female gender, and persons with caring responsibilities experiencing the most severe manifestations [ 131 ]. In a systematic review and meta-analysis of mental issues due to COVID-19, it was shown that stress levels associated with the pandemic were more prevalent in university faculty compared to other educators such as school teachers.…”
Section: Review Of Factors Contributing To Mental Health Concerns Amo...mentioning
confidence: 99%
“…Numerous reports have documented the psychological toll created by COVID‐19 on medical personnel, including elevated symptoms of posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and anxiety using validated scores on self‐report measures (e.g., Marvaldi et al., 2021). There is consensus that the workplace during early months of COVID‐19 held many opportunities for trauma exposure for health care professionals given the experience of patient deaths and exposure to a life‐threatening virus which, if contracted, could be lethal for an individual and their household members (e.g., Ashby et al., 2021; Goldstein et al., 2022). A recent meta‐analysis examining studies of medical professionals suggested elevated rates of anxiety symptoms, with higher prevalence rates among nurses (27%) compared with physicians (17%; Santabárbara et al., 2021).…”
mentioning
confidence: 99%